2023
DOI: 10.1002/path.6068
|View full text |Cite
|
Sign up to set email alerts
|

Liver insulin‐like growth factor‐1 mediates effects of low‐intensity vibration on wound healing in diabetic mice

Abstract: Chronic wounds in diabetic patients are associated with significant morbidity and mortality; however, few therapies are available to improve healing of diabetic wounds. Our group previously reported that low‐intensity vibration (LIV) could improve angiogenesis and wound healing in diabetic mice. The purpose of this study was to begin to elucidate the mechanisms underlying LIV‐enhanced healing. We first demonstrate that LIV‐enhanced wound healing in db/db mice is associated with increased IGF1 protein levels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…30,31 Extensively studied since the 1980s, 32 recent research, particularly in animal models, has highlighted its potential in wound healing [32][33][34][35] Studies have shown that WBV accelerates wound closure, re-epithelialization, and angiogenesis, especially in diabetic hard-to-heal animal models, by reducing tissue hypoxia and promoting tissue regeneration. [36][37][38][39] Notably, low-frequency and low-intensity WBV have been effective in improving both wound closure and healing quality, making it a promising therapeutic avenue for hard-to-heal wounds.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…30,31 Extensively studied since the 1980s, 32 recent research, particularly in animal models, has highlighted its potential in wound healing [32][33][34][35] Studies have shown that WBV accelerates wound closure, re-epithelialization, and angiogenesis, especially in diabetic hard-to-heal animal models, by reducing tissue hypoxia and promoting tissue regeneration. [36][37][38][39] Notably, low-frequency and low-intensity WBV have been effective in improving both wound closure and healing quality, making it a promising therapeutic avenue for hard-to-heal wounds.…”
Section: Introduction Backgroundmentioning
confidence: 99%